2016
DOI: 10.1167/iovs.15-18975
|View full text |Cite|
|
Sign up to set email alerts
|

Cupping in the Monkey Optic Nerve Transection Model Consists of Prelaminar Tissue Thinning in the Absence of Posterior Laminar Deformation

Abstract: PurposeTo use optical coherence tomography (OCT) to test the hypothesis that optic nerve head (ONH) “cupping” in the monkey optic nerve transection (ONT) model does not include posterior laminar deformation.MethodsFive monkeys (aged 5.5–7.8 years) underwent ONH and retinal nerve fiber layer (RNFL) OCT imaging five times at baseline and biweekly following unilateral ONT until euthanization at ∼40% RNFL loss. Retinal nerve fiber layer thickness (RNFLT) and minimum rim width (MRW) were calculated from each pre- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…In a recent study comparing eyes with compressive optic neuropathy and eyes with POAG, Hata et al 35 found that despite having the same cup-to-disc ratios in both groups, ALD was smaller in compressive optic neuropathy than in POAG eyes but similar to that in control healthy eyes. In line with our results, in an experimental animal study, Ing et al 36 showed that while RNFL thickness demonstrated profound thinning, ALD was not displaced posteriorly approximately 50 days following optic nerve transection. As these findings are in contrast to OCT detection of significant laminar deformation after chronic IOP elevation, 33 the authors proposed that posterior laminar deformation following connective tissue damage should be included in the definitions used to distinguish glaucomatous and nonglaucomatous optic neuropathy in the monkey eye.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a recent study comparing eyes with compressive optic neuropathy and eyes with POAG, Hata et al 35 found that despite having the same cup-to-disc ratios in both groups, ALD was smaller in compressive optic neuropathy than in POAG eyes but similar to that in control healthy eyes. In line with our results, in an experimental animal study, Ing et al 36 showed that while RNFL thickness demonstrated profound thinning, ALD was not displaced posteriorly approximately 50 days following optic nerve transection. As these findings are in contrast to OCT detection of significant laminar deformation after chronic IOP elevation, 33 the authors proposed that posterior laminar deformation following connective tissue damage should be included in the definitions used to distinguish glaucomatous and nonglaucomatous optic neuropathy in the monkey eye.…”
Section: Discussionsupporting
confidence: 92%
“…Lee et al 24 also found that prelaminar thickness was less in glaucomatous patients than in NAION patients. Similarly, Ing et al 36 found prelaminar tissue thinning following experimental optic nerve transaction. Lack of optic disc excavation and changes in optic rim in atrophic optic nerve due to NAION have been described in previous studies.…”
Section: Discussionmentioning
confidence: 80%
“…Prelaminar thinning results from thinning of the prelaminar tissues due to physical compression and/or loss of retinal ganglion cell axons without important laminar or ONH connective tissue involvement. Ing et al 17 reported anterior rather than posterior laminar deformation postoptic nerve transection in a monkey model due to profound thinning of the RNFL and prelaminar rim tissue, which shows ‘prelaminar’ or ‘shallow’ forms of ‘cupping’ in ‘non-glaucomatous’ optic neuropathies that are not accompanied by laminar deformation. In our study, both glaucomatous and non-glaucomatous cupping groups had similar thinning in PLT than control eyes.…”
Section: Discussionmentioning
confidence: 99%
“…However, we also emphasize that, to date, selectively killing RGC soma or axons alone, by whatever mechanism, has not been shown to create a glaucomatous optic neuropathy (i.e. glaucomatous ONH cupping) (Brooks et al, 2004; Chauhan et al, 2004; Ing et al, 2016; Joachim et al, 2013; Wax et al, 2008; Yang et al, 2014a). …”
Section: 0 Introductionmentioning
confidence: 85%
“…In addition, they confirm that early glaucomatous damage to the monkey ONH includes both neural and connective tissue components (Yang et al, 2007a; Yang et al, 2009a). This finding is important because it identifies OCT-detectable ONH connective tissue endpoints for other monkey experimental optic neuropathy models including chronic experimental CSFp lowering (Yang et al, 2014a), endothelin (Brooks et al, 2004), optic nerve transection (Ing et al, 2016) and anterior ischemic optic neuropathy (AION) (Miller et al, 2014) which are discussed in Section 4.0, below.…”
Section: 0 Experimental Evidence Of Onh Connective Tissue Deformatimentioning
confidence: 99%